Social risks of internet activity of virtual communities - N. S. Zimova; E. V. Fomin (Цифровая социология)
The article studies a phenomenon of Internet activism of virtual communities, identifies their essence and characteristics, and analyzes possible social risks of their activities. The authors substantiate a position that such communities are able to quickly mobilize users for coordinated actions in social reality, responding to economic, social, political, and cultural events. These activities are generally oppositional to established values and social institutions and carry social risks. Based on the approaches of G. Rheingold, N. Baym, and B. Wellman, the authors propose, justify, and develop their own typology of virtual communities depending on their Internet activity. The article focuses on the activity of explicitly virtual (latently real) communities that influence social reality through protest performances, flash mobs, spam attacks, Internet actions, etc. Using the case study method, the authors examine Reddit’s r/wallstreetbets and V.V. Pozdnyakov’s Muzhskoe Gosudarstvo Telegram communities. Based on the analysis of the Internet activism practices of virtual communities, risks and threats of uncontrolled and spontaneous actions on their part have been demonstrated. As a result, need for multidimensional analysis of virtual communities by government agencies, business representatives, and research scientific centers has been noted.